Literatur Review : Implementasi Manajemen Mutu Dan Kualitas Layanan Di Unit Laboratorium - Modestus La'a; Vip Paramarta; Marianne Lukytha Tangdililing (STIKes Ibnu Sina Ajibarang, 2023)
This comprehensive review synthesizes findings from various journals on the management of quality and service in laboratory units within the healthcare context. The synthesis reveals the importance of service quality and its impact on patient satisfaction and service effectiveness. Key findings include the positive influence of service quality dimensions such as reliability, physical evidence, and friendliness on patient satisfaction. Additionally, the interconnection between service quality and adherence to health standards and regulations is emphasized, underlining the significance of compliance for service improvement. External factors, such as government regulations and health policies, are identified as potential influencers of service quality, adding complexity to quality management. Practical implications for healthcare policies and practices are highlighted, suggesting improvements in human resource training, service processes, and infrastructure. Recommendations include strengthening human resource training through regular and ongoing programs, optimizing service processes by thorough workflow evaluations, and ensuring strict compliance with health standards. Furthermore, the integration of technological innovations is proposed as a progressive step toward enhancing service efficiency and result accuracy. The implementation of laboratory information systems, modern equipment, and related applications is suggested to advance service quality. The establishment of a regular monitoring and evaluation system, including internal audits, routine performance reviews, and patient feedback collection, is crucial for continuous improvement. Collaboration with external entities, such as health oversight agencies and laboratory professional associations, is advocated for robust guidance and support. Encouraging research and innovation in quality management and laboratory service is recommended to enhance understanding of new technology applications, quality maintenance strategies, and policy impact evaluation. By implementing these suggestions, laboratory units are expected to continually enhance service quality and ensure optimal patient satisfaction.